Bitter gourd (Momordica charantia) possess developmental toxicity as revealed by screening the seeds and fruit extracts in zebrafish embryos - Muhammad Farooq Khan; Nael Abutaha; Fahd A. Nasr; Ali S. Alqahtani; Omar M. Noman; Mohammad A. M. Wadaan (BMC Complementary and Alternative Medicine, 2019)
Abstract Background Bitter gourd (Momordica charantia) has attracted the focus of researchers owing to its excellent anti-diabetic action. The beneficial effect of Momordica charantia on heart has been reported by in vitro and in vivo studies. However the developmental toxicity or potential risk of M. charantia on fetus heart development is largely unknown. Hence this study was designed to find out the developmental toxicity of M. charantia using zebrafish (Danio rerio) embryos. Methods The crude extracts were prepared from fruit and seeds of M. charantia. The Zebrafish embryos were exposed to serial dilution of each of the crude extract. The biologically active fractions were fractionated by C18 column using high pressure liquid chromatography. Fourier-transform infrared spectroscopy and gas chromatography coupled with mass spectrophotometry was done to identify chemical constituents in fruit and seed extract of M. charantia. Results The seed extract of M. charantia was lethal with LD50 values of 50 μg/ml to zebrafish embryos and multiple anomalies were observed in zebrafish embryos at sub-lethal concentration. However, the fruit extract was much safe and exposing the zebrafish embryos even to 200 μg/ml did not result any lethality. The fruit extract induced severe cardiac hypertrophy in treated embryos. The time window treatment showed that M. charantia perturbed the cardiac myoblast specification process in treated zebrafish embryos. The Fourier-transform infrared spectroscopy analyses revealed diverse chemical group in the active fruit fraction and five new type of compounds were identified in the crude seeds extract of M. charantia by gas chromatography and mass spectrophotometry. Conclusion The teratogenicity of seeds extract and cardiac toxicity by the fruit extract of M. charantia warned that the supplementation made from the fruit and seeds of M. charantia should be used with much care in pregnant diabetic patients to avoid possible damage to developing fetus.